Tanggap Varietas Kacang Hijau terhadap Cekaman Salinitas - Taufiq, Abdullah; Purwaningrahayu, Runik Dyah (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2013)
The response of mungbean varieties to salinity stress was evaluated using pot experiment in green house at Indonesian Legumes and Tuber Crops Research Institute in Malang from July to September 2012. Two factors of sixty treatments were arranged in a randomized complete block design, replicated four times. The first factor was six water salinity levels, namely check (ECw 0.5 dS/m), 4.0, 7.1, 10.1, 13.1, and 15.8 dS/m. The second factor was ten mungbean varieties, namely Vima 1, Kutilang, Sampeong, Perkutut, Murai, Kenari, Sriti, Merpati, Betet, dan Walet. Data collection consisted of grain yield and yield components, plant biomass, chlorophyll content index (CCI), plant height, leaf area, and relative water content of leaf (RWC). The results showed that increasing water salinity increased soil salinity (ECs). Increasing salinity did not significantly affect total leaf area per plant, but significantly reduced root dry weight, CCI, number of filled pods, pods and seed dry weight per plant, and weight of 100 grains. Those variables were reduced by 11% to 37% at ECs of 2.65 dS/m. Plant height decreased by 10%, shoot dry weight by 22% and leaf relative water content by 10% at ECs of 6.27, 3.29 and 8.81 dS/m, consecutively. Chlorophyll content index, grain yield and yield components were more sensitive to salinity stress than were plant height, shoot biomass, and leaf area. Based on grain yield reduction, there was different salinity tolerance among the mungbean varieties tested. Vima 1 variety was tolerant up to ECs of 6.40-12.49 dS/m. Murai, Kenari, Sriti, and Betet varieties were tolerant up to ECs of 2.87-5.68 dS/m. Kutilang, Sampeong, Perkutut, Merpati, and Walet varieties were tolerant up to ECs of 1.79-2.65 dS/m. There was no indication that the degree of tolerance of these varieties related to Na and K content in the shoot and root of the plant at 37 days after planting. The critical ECs value for mungbean varietal testing was 1.79-2.65 dS/m.